2022
DOI: 10.1002/deo2.180
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early‐stage COVID‐19 pandemic on the diagnosis and treatment of gastric cancer: A cross‐sectional study using a large‐scale cancer registry in Hiroshima, Japan

Abstract: Background After the confirmation of coronavirus infection in Japan, a behavioral change caused people and physicians to refrain from visiting hospitals or undergoing examinations. This study aimed to assess how the trend of diagnosis in gastric cancers changed, and how it affected the therapeutic strategies and the interval from diagnosis to treatment during the COVID‐19 pandemic. Methods We use 15 cancer‐designated hospitals’ registries in Hiroshima, Japan. The target period was March to December 2020, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…This is likely to be due to factors such as a decrease in the overall number of hospital visits following the start of the COVID-19 pandemic and a decrease in the waiting time before surgery. 11,25 The number of beds in the acute care wards occupied by patients with COVID-19 remained below 5%. 26 Regarding the changes in treatment options, there was a decrease in open surgery and an increase in laparoscopic surgery during the pandemic period, which might be due to the results of a randomized control trial in Japan reported in 2016, showing non-inferiority of laparoscopic surgery to open surgery.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This is likely to be due to factors such as a decrease in the overall number of hospital visits following the start of the COVID-19 pandemic and a decrease in the waiting time before surgery. 11,25 The number of beds in the acute care wards occupied by patients with COVID-19 remained below 5%. 26 Regarding the changes in treatment options, there was a decrease in open surgery and an increase in laparoscopic surgery during the pandemic period, which might be due to the results of a randomized control trial in Japan reported in 2016, showing non-inferiority of laparoscopic surgery to open surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to what might be assumed, the interval from diagnosis to laparoscopic surgery and chemotherapy was shorter during the COVID‐19 pandemic period, unlike that in previous studies. This is likely to be due to factors such as a decrease in the overall number of hospital visits following the start of the COVID‐19 pandemic and a decrease in the waiting time before surgery 11,25 . The number of beds in the acute care wards occupied by patients with COVID‐19 remained below 5% 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no trajectory of an increase in advanced rectal cancer cases [10]. Kodama et al also reported that even under COVID-19 pandemic, if we should be an awareness of cancer screening and endoscopic follow-up, cancer screening played a signi cant role in the decline in cancer diagnosis [11]. However, as with gynecological cancers, the number of cases may increase after 2021, and caution should be exercised for us.…”
Section: Discussionmentioning
confidence: 99%